2001
DOI: 10.1381/096089201321577884
|View full text |Cite
|
Sign up to set email alerts
|

Pre-operative Predictors of Weight Loss at 1-Year after Lap-Band® Surgery

Abstract: Important physical factors have been found to influence the rate of weight loss. Those with increased age, pain, physical disability and insulin resistance have a great deal to gain from weight loss. Although this study has identified factors that are associated with less weight loss, we have not found any factor that predicts an unacceptably low weight loss and thus provides a contraindication to Lap-Band placement. The findings of this study allow us to set more realistic goals for the rate of weight loss in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
93
4
3

Year Published

2002
2002
2014
2014

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 149 publications
(110 citation statements)
references
References 23 publications
10
93
4
3
Order By: Relevance
“…%ΔL: H) shows a predictive capacity as strong as the initial BMI, which, up to now, was considered one of the best predictors of weight loss after surgery [25]. In fact, when separately analysed, %ΔL: H, as well as preoperative BMI, explained over 40% of the weight reduction variability (Figs.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…%ΔL: H) shows a predictive capacity as strong as the initial BMI, which, up to now, was considered one of the best predictors of weight loss after surgery [25]. In fact, when separately analysed, %ΔL: H, as well as preoperative BMI, explained over 40% of the weight reduction variability (Figs.…”
Section: Discussionmentioning
confidence: 83%
“…Thus, BMI plays a major role during the early postoperative period, whereas its influence becomes much weaker later on. Dixon et al [25] demonstrated that preoperative BMI is strongly related to BMI measured 1 year, but not 2 years, after surgery. This suggests that initial BMI does not influence weight maintenance or regain.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, younger subjects realize the largest weight reduction, when compared to their respective older counterparts (P < 0.0001 between the groups with initial body weight higher than 120 kg P < 0.0005 between the groups with an initial body weight lower than 120 kg). Younger subjects have been reported to achieve a more satisfactory body weight loss (Dixon et al, 2001). However, to our knowledge, no study has related a better capacity of younger patients either in reducing food intake after bariatric surgery or in complying with a hypocaloric diet.…”
Section: Discussionmentioning
confidence: 95%
“…We have previously shown that reduced insulin sensitivity and the conditions associated with it are associated with a lower rate of weight loss after LAGB surgery (26). The reason for this is unknown but may relate to reduced energy expenditure in diabetic subjects or an effect of hyperinsulinemia on central control of energy balance, increasing appetite and, thus, energy intake.…”
Section: Sleep Disturbancementioning
confidence: 99%